South Africa implements a national strategy to support community seed banks - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
Traditional practices of maintaining indigenous biodiversity are in danger as a result of stresses caused by climate change and human activities. South Africa’s Department of Agriculture, Forestry and Fisheries, in collaboration with Bioversity International, implements a national community seed bank strategy to support smallholders in preservation and multiplication practices for seeds of local importance. Women farmers are playing a key role in the management of the pilot community seed banks.